Bullwhip effect under substitute products - Duan, Yongrui; Yao, Yuliang; Huo, Jiazhen (Journal of Operations Management, 2015)
AbstractUsing a large‐scale, product‐level dataset collected from a supply chain dyad, we examine the effect of own and substitute products on a focal product's bullwhip effect and estimate the existence and magnitude of the bullwhip effect at the product level. We find that, under substitute products, the bullwhip effect is not only affected by a product's own factors but also by those of its substitute products. An increase in the number of own price changes is associated with a decrease in the bullwhip effect in terms of the direct effect but with an increase in the bullwhip effect in terms of the total effect, and increases in the number of price changes of substitute products and own stockouts are associated with increases in the bullwhip effect. The potential effects for own price changes, price changes of substitute products and own stockouts are as much as 59.51%, 95.06% and 66.11%. We also find that the bullwhip effect is prevalent and very intensive at the product level. We discuss the theoretical and managerial implications of the findings.